2010
DOI: 10.1017/s0022112010000571
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale geometric analysis of Lagrangian structures in isotropic turbulence

Abstract: We report the multi-scale geometric analysis of Lagrangian structures in forced isotropic turbulence and also with a frozen turbulent field. A particle backwardtracking method, which is stable and topology preserving, was applied to obtain the Lagrangian scalar field φ governed by the pure advection equation in the Eulerian form ∂ t φ + u · ∇φ = 0. The temporal evolution of Lagrangian structures was first obtained by extracting iso-surfaces of φ with resolution 1024 3 at different times, from t = 0 to t = T e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 55 publications
1
30
0
1
Order By: Relevance
“…Finally, this appears to move towards a stationary stage, which might be controlled by O (B(t)), as shown in figure 12 and implied in (5.6). In contrast, Yang et al (2010) showed that a Lagrangian field, starting from an arbitrary initial condition with a moderate |λ ω0 | in stationary isotropic turbulence, appeared to exhibit a tendency to move towards a vortex-surface field of the evolving flow, but this is mitigated by cumulative viscous effects. In the TG flow, from an arbitrary initial Lagrangian field φ 0 = sin x sin y sin z, we also observed a similar decreasing trend for |λ ω | in figure 12.…”
Section: 1mentioning
confidence: 88%
See 2 more Smart Citations
“…Finally, this appears to move towards a stationary stage, which might be controlled by O (B(t)), as shown in figure 12 and implied in (5.6). In contrast, Yang et al (2010) showed that a Lagrangian field, starting from an arbitrary initial condition with a moderate |λ ω0 | in stationary isotropic turbulence, appeared to exhibit a tendency to move towards a vortex-surface field of the evolving flow, but this is mitigated by cumulative viscous effects. In the TG flow, from an arbitrary initial Lagrangian field φ 0 = sin x sin y sin z, we also observed a similar decreasing trend for |λ ω | in figure 12.…”
Section: 1mentioning
confidence: 88%
“…Here, N p should be greater than the grid number N of the velocity field, i.e. the resolution of the Lagrangian field should be higher than the velocity field to capture some nearly singular Lagrangian structures in the evolution (Yang et al 2010). Then, particles are released and their trajectories calculated by solving (4.2) backwards in time.…”
Section: Lagrangian Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Using (2.18) and ∂ω(x, t)/∂τ = 0 at fixed t, and following a line of analysis applied in Yang, Pullin & Bermejo-Moreno (2010) and to a Lagrangian field, we can show, after some algebra, that…”
Section: Convergence Of Numerical Solutionsmentioning
confidence: 99%
“…This issue was discussed by Green, Rowley & Haller (2007) who showed the evolution of single vortex-like structures into a packet of similar structures in turbulent channel flow by identifying 'Lagrangian coherent structures' (Haller 2001). Yang, Pullin & Bermejo-Moreno (2010) illustrated and quantified the evolutionary geometry in the breakdown of initially large-scale Lagrangian structures in isotropic turbulence using a multi-scale geometric analysis.…”
Section: Introductionmentioning
confidence: 99%